FAILURE MODES AND EFFECT ANALYSIS METHOD ON A DRILL STRING COMPONENTS - Kharisma, Aji A. (Jurnal Ilmiah Informatika Komputer, 2017)
This research is focused on the Rotary shoulder connection (Bit sub), 5” OD Heavy Weight Drill Pipe and 8 ” OD  Spiral Drill Collar in the form of pitting thread, galled thread and damage of thread which is conducted by using FMEA (Failure Mode and Effect Analysis) method. The objectives of this research are to determine the risk priority number and a risk ranking  ( RPN : Risk Priority number )  through the data of failure which is occur on pitting thread, galled thread and damage of thread on the Rotary shoulder connection (Bit sub), 5” OD Heavy Weight Drill Pipe and 8 ” OD  Spiral Drill Collar. The result shows that the risk ranking can be founded with the condition acceptable risk with the RPN criteria   < 35 ( Low Risk ) and RPN in the range of 35 - 124 ( medium risk ) and the result risk ranking or high risk with criteria RPN in the range of 124 - 1000 the condition is unacceptable. The result from value of RPN after reducing from the three of failure on the Rotary shoulder connection (Bit sub), 5” OD Heavy Weight Drill Pipe and 8 ” OD  Spiral Drill Collar can be accepted with the criteria of RPN in the range of 35 - 124 (medium risk). Keywords : FMEA ( Failure Mode and Effect Analysis ), Drill String Components, RPN ( Risk Priority Number ), Maintenance and preventive control.